2022
DOI: 10.2807/1560-7917.es.2022.27.35.2100883
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific associations between underlying health conditions and hospitalisation, death and in-hospital death among confirmed COVID-19 cases: a multi-country study based on surveillance data, June to December 2020

Abstract: Background Underlying conditions are risk factors for severe COVID-19 outcomes but evidence is limited about how risks differ with age. Aim We sought to estimate age-specific associations between underlying conditions and hospitalisation, death and in-hospital death among COVID-19 cases. Methods We analysed case-based COVID-19 data submitted to The European S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The value of surveillance systems during the COVID-19 pandemic cannot be overstated (9). Insights from these systems and other hospital-based studies have been useful in identifying those at increased risk for severe outcomes and informing both pharmaceutical and non-pharmaceutical interventions against the disease(6, 25, 26, 27, 28, 29). Our study found that patients admitted between May 2020 and December 2022 with SARI had a higher mortality rate, especially those with COVID-19, compared to their non-SARI counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of surveillance systems during the COVID-19 pandemic cannot be overstated (9). Insights from these systems and other hospital-based studies have been useful in identifying those at increased risk for severe outcomes and informing both pharmaceutical and non-pharmaceutical interventions against the disease(6, 25, 26, 27, 28, 29). Our study found that patients admitted between May 2020 and December 2022 with SARI had a higher mortality rate, especially those with COVID-19, compared to their non-SARI counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on routine clinical data and documentation practices which differ by individual and by site limited the study’s ability to explore the effect of other known risk factors for death in COVID-19 such as multiple comorbidities at admission, social habits e.g., smoking, HIV infection or exposure to previous medication (6, 10, 29). While completion of demographic parameters was high, poor documentation practices and missing data for clinical parameters and investigations limited the number of patients included in the multivariable analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The probabilities of severe disease , though learned from the fitting process defined below, are constrained to lie within the following intervals which have widths twice the size of the estimates in (18). Similarly, we learn and constrain them to lie in intervals [0, 2 q a ] where q a represents the total deaths divided by the total hospitalizations in age group a in a given wave, obtained from (23).…”
Section: Additional Program Implementation Detailsmentioning
confidence: 99%
“…Recall that those with severe disease eventually require hospitalization. (18) provide estimates for the probabilities of infected and unvaccinated individuals who are hospitalized (1% for 0 to 18, 7% for 19 to 64, and 30% for 65+). These estimates do not quite correspond to p severe av in our model, which is a conditional probability on symptomatic disease.…”
Section: (I) Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation